Variation in the Three-Dimensional Histomorphometry of the Normal Human Optic Nerve Head With Age and Race: Lamina Cribrosa and Peripapillary Scleral Thickness and Position - Girkin, Christopher A. (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: This study quantified the thickness and depth of the lamina cribrosa (LC) and peripapillary scleral thickness in high-resolution three-dimensional (3D) fluorescent reconstructions of the optic nerve head (ONH) in eyes from donors of African (AD) and European descent (ED). METHODS: A total of 64 eyes (45 ED, 19 AD) from 51 normal donors were obtained within 6 hours of death and fixed at 10 mm Hg of pressure. The optic nerve head was trephined from the globe and digitally reconstructed at 1.5 × 1.5 × 1.5 μm voxel resolution with an automated episcopic fluorescence technique. The load-bearing ONH connective tissue surfaces were manually delineated in 3D using custom software. RESULTS: The lamina cribrosa and peripapillary sclera were significantly thinner in AD eyes adjusting for age and sex (LC was 24 ± 11 μm thinner; P = 0.0350; scleral was 56 ± 22 μm thinner; P = 0.0097). The lamina cribrosa was significantly thinner in females (23 ± 11 μm thinner; P = 0.0425). Age was not significantly associated with any morphologic parameter in the ED group. However, increasing age was associated with an increase in scleral thickness (1.3 μm/year, P = 0.0499) and an increase in LC depth (2.3 μm/year, P = 0.0035) in the AD group. The sclera was thickest in the superior and temporal regions while the LC was thinnest superiorly. CONCLUSIONS: Substantial sectorial and racial differences in LC and scleral morphology were observed, as well as increasing LC depth and scleral thickness with age in the AD group. Results suggest greater age-related remodeling of the load-bearing ONH connective tissues in eyes from AD individuals that could explain, in part, the greater predilection to glaucomatous injury seen in aged AD populations.